Spiritual Well-Being and Resilience of Emerging Adults of a Catholic College in Central Negros - Calamba, Patrick Calseña; Magallanes, Celo I. (Technium Social Sciences Journal, 2023)
Finding one’s meaning and purpose in life depends on one’s spiritual well-being. This is connected to resilience, which is a dynamic attribute of overcoming difficult conditions and a growth mindset. Thus, this descriptive, comparative, and correlational study wanted to know the degree of spiritual well-being and the level of resilience of emerging adults of a Catholic college in Central Negros. Spiritual Well-Being Scale and Resilience Scale standardized questionnaires were used among the 237 respondents. The results show that the emerging adults’ degree of spiritual well-being is moderate, indicating that they have a fair sense of purpose in life. Likewise, the level of resilience yielded a moderate result. Further, results show a significant relationship between spiritual well-being and resilience. The findings typically indicate that emerging adults have a moderate sense of life’s pleasure and purpose as well as the ability to bounce back from difficult situations. The results show that they have clung to God somewhat, but not entirely, and that their sense of purpose and direction in life are still unclear. They are still halfway to reaching their full potential and defining a clear life purpose. The study recommends the creation of a counseling program for the development of emerging adults.